Line Dance Phenomenon on Heart Rate of Elderly 40-60 Years Old Through TikTok Media - Nabila Putri Ayu Maharani Nabila; Rachmi Marsheilla Aguss (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aimed to explore the use of TikTok social media as a supportive tool in understanding the motivations of older adults aged 40-60 years that influence heart rate during line dance exercise. A total of 40 respondents were involved in this study, consisting of 75% women and 25% men. The research method used was qualitative with a survey approach, through a Google Form shared via WhatsApp. Data collection was carried out for two consecutive days at Sanggar Kenanga and Lapangan Saburai, Lampung. The research instrument included five main indicators of elderly participation in line dance exercises. The results showed that 70% of the elderly were familiar with line dancing as a form of physical activity. However, 75% of them admitted to having difficulty following the rhythm of the music while dancing. On the social side, 70% of the elderly invited others to participate, and 80% felt the physical benefits of this activity. Interestingly, 75% of older adults actively seek movement guidance through videos on TikTok. The average motivation of older adults to participate in line dancing was recorded at 74%, categorized as “often”. These findings confirm that TikTok can be an effective medium to promote physical activities that support physical and social health for older adults.